2004
DOI: 10.1073/pnas.0305375101
|View full text |Cite
|
Sign up to set email alerts
|

Infraslow oscillations modulate excitability and interictal epileptic activity in the human cortex during sleep

Abstract: Human cortical activity has been intensively examined at frequencies ranging from 0.5 Hz to several hundred Hz. Recent studies have, however, reported also infraslow fluctuations in neuronal population activity, magnitude of electroencephalographic oscillations, discrete sleep events, as well as in the occurrence of interictal events. Here we use direct current electroencephalography to demonstrate large-scale infraslow oscillations in the human cortex at frequencies ranging from 0.02 to 0.2 Hz. These oscillat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
417
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 450 publications
(445 citation statements)
references
References 36 publications
24
417
1
3
Order By: Relevance
“…Furthermore, we were not limited to only sensorimotor ROIs in our approach. The interconnected nature of the activity structure of infraslow and slow activity is consistent with a cross-frequency phase-amplitude coupling relationship that has previously been indicated for infraslow fluctuations in EEG and MEG recordings in human subjects [13][14][15]60 .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Furthermore, we were not limited to only sensorimotor ROIs in our approach. The interconnected nature of the activity structure of infraslow and slow activity is consistent with a cross-frequency phase-amplitude coupling relationship that has previously been indicated for infraslow fluctuations in EEG and MEG recordings in human subjects [13][14][15]60 .…”
Section: Discussionsupporting
confidence: 87%
“…In the developing brain, electrophysiological infraslow activity in the form of neuronal activity transients or bursting activity has been linked with the development of neuronal networks 11,12 , whereas in the adult brain, infraslow activity has been demonstrated to synchronize with higher-frequency brain activity 13,14 and to correlate to variability in behavioural performance 15,16 . Renewed focus on the nature of spontaneous resting-state infraslow activity has been precipitated due to an immense proliferation of functional neuroimaging studies that have revealed much about the brain's functional organization and have identified what has been described as the brain's Default Mode Network (DMN) 17 , a network of brain structures that are coherently, highly active at rest and reduced during active task performance 18 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless the limits of the EEG frequency bands are fuzzy. Ultra-slow (near-DC) oscillations (Aladjalova, 1957;Vanhatalo et al, 2004) and ultra-fast frequency components have also been described. Here we concentrate primarily on the fast frequency components.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, very low frequency oscillations (VLFOs, <0.5 Hz) have been recorded in the EEG of preterm neonates, during epileptic seizure activity (Vanhatalo et al, 2005), in attention deficit hyperactivity disorder (ADHD) (Helps et al 2008(Helps et al , 2010, and during sleep stages (Steriade et al, 1993;Vanhatalo et al, 2004). These VLFOs, first observed by Biswal et al (1995) within the motor cortex in functional magnetic resonance imaging (fMRI) blood oxygenation level dependent (BOLD) signals during rest, appear to be intrinsically generated by the brain, are most prominent during rest and may allow temporal synchronisation to promote communication across diverse brain networks (Buzsáki and Draguhn, 2004;Fransson, 2005Fransson, , 2006.…”
Section: Introductionmentioning
confidence: 99%